If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying X + (10 + x) = 64 Remove parenthesis around (10 + x) X + 10 + x = 64 Reorder the terms: 10 + X + x = 64 Solving 10 + X + x = 64 Solving for variable 'X'. Move all terms containing X to the left, all other terms to the right. Add '-10' to each side of the equation. 10 + X + -10 + x = 64 + -10 Reorder the terms: 10 + -10 + X + x = 64 + -10 Combine like terms: 10 + -10 = 0 0 + X + x = 64 + -10 X + x = 64 + -10 Combine like terms: 64 + -10 = 54 X + x = 54 Add '-1x' to each side of the equation. X + x + -1x = 54 + -1x Combine like terms: x + -1x = 0 X + 0 = 54 + -1x X = 54 + -1x Simplifying X = 54 + -1x
| 2x+16+x+41=180 | | 7x-9=x-15 | | y=-2*-2+2*-2-7 | | 66x+20x=400+66x | | y=-2*-2+2-7 | | y=0*0+2*0-7 | | (66+20)x=400+66x | | n=-39-5m | | 2(2x+15)=190 | | 5x-4x+3=9-3 | | 8x-21+23x-16=180 | | -25+3x=-7 | | (9+22)9=(12+c)12 | | -3(x+2)+2(3x-3)=5 | | (5m-2)(5m+2)= | | -5(-8+8x)=-3+3x | | 66+20x=400+66x | | 3x^3-6x^2-15X+18=0 | | 66+20x=400+6x | | 5x-3+2x+5=9x+6 | | 3=1.2+-0.2y | | 14x^3-8x^2+18x= | | -25=5(a-8) | | (x-30)(x-30)(x-30)=540 | | 3x+4+3x-6=8x+4 | | -14=-6+4e | | 29=-x+7x-1 | | 3x+5+3x-6=10x-2 | | 2=1.2+-0.2y | | 30x+5=64 | | 1=1.2+-0.2y | | 42x^2-480x-2463=0 |